1988
DOI: 10.1007/bf00409381
|View full text |Cite
|
Sign up to set email alerts
|

Renal function of chrome-plating workers and welders

Abstract: The influence of occupational exposure to water-soluble chromium (VI) on renal function was examined. In male chrome-plating workers (n = 29), stainless steel welders (n = 45), boilermakers (n = 18) and a control group of workers (n = 71), the level of chromium in the urine (Cr-U), the chromium clearance, and sensitive renal function parameters were determined. The glomerular-function parameters of the chrome-plating workers (Cr-U 1 to 34 micrograms/g creat) and welders (Cr-U 1 to 62 micrograms/g creatine) app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…In particular, a mean urinary chromium concentration has been reported as 31 5 ,g/l (creatinine concentrations not Table 4 Mean (SEM) chromium concentrations in biological matrices ofsmokers and non-smokers from the group exposed to chromium pg/g creatinine. 30 Thus, it can be seen that in comparison with most of these reported studies, the chromium concentrations in our study are low (table 2). The low urinary concentrations are consistent with the low estimated airborne concentrations of chromium that the workforce are exposed to (< 0.01 mg/m3).…”
Section: Discussioncontrasting
confidence: 46%
“…In particular, a mean urinary chromium concentration has been reported as 31 5 ,g/l (creatinine concentrations not Table 4 Mean (SEM) chromium concentrations in biological matrices ofsmokers and non-smokers from the group exposed to chromium pg/g creatinine. 30 Thus, it can be seen that in comparison with most of these reported studies, the chromium concentrations in our study are low (table 2). The low urinary concentrations are consistent with the low estimated airborne concentrations of chromium that the workforce are exposed to (< 0.01 mg/m3).…”
Section: Discussioncontrasting
confidence: 46%
“…Excessive urinary excretion of P2-microglobulin, a specific proximal tubule brush border protein (BB-50) and an extra-renal enzyme, retinol-binding protein, have been reported among some chrome platers and welders (Tables 1 and 2), but not in others (16)(17)(18). The reasons for these contradictory findings are not clear but may relate to the absence of a reliable measure of cumulative past absorption and un- LMW proteinuria indicates tubular dysfunction and is often called "tubular proteinuria."…”
Section: Tubular Proteinuriamentioning
confidence: 99%
“…Tubular proteinuria occurs after a wide variety of physiologic stresses, is usually reversible, and cannot by itself be considered evidence of chronic renal disease. Progression to renal failure has not been observed among chrome workers exhibiting tubular proteinuria (17,18). Although acute tubular necrosis induced by single large doses of chromium is preceded by tubular proteinuria, there is no evidence that tubular proteinuria resulting from repeated small doses results in permanent renal damage, i.e., chronic renal disease.…”
Section: Tubular Proteinuriamentioning
confidence: 99%
“…In fact, the betajmicroglobulin excretion in these two studies was found to be decreased in the exposed workers. Verschoor et al (10) and Zschiesche et al (8) examined workers with a lower exposure to chromium (mean urinary chromium < 10.8 nmol· mmol:' creatinine) and also found no indication of a renal effect.…”
Section: Discussionmentioning
confidence: 99%